2002
DOI: 10.1046/j.1359-4117.2002.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe folate restriction results in depletion of and alteration in the composition of the intracellular folate pool, moderate sensitization to methotrexate and trimetrexate, upregulation of endogenous DHFR activity, and overexpression of metallothionein II and folate receptor alpha that, upon folate repletion, confer drug resistance to CHL cells

Abstract: DC-3F/FA3 cells (FA3) were derived from antifolate-sensitive CHL cells by selection for growth in folate-free media containing 15 pM [6S]-5CHOFH4. These cells undergo a 30-fold decrease in intracellular folates, overexpress folate receptor alpha (FR alpha) and metallothionein II, and display increased sensitivity to the dihydrofolate reductase (DHFR) targeted anti-folates methotrexate (MTX) and trimetrexate (TMTX), which can be attributed primarily to the folate pool status. Upon folate repletion by growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…FRα-mediated transport of MTX is also evident [28]. Reports on low folate induced upregulation of FR support the inverse relationship between FA concentration and FR expression [29]. In either case, MTX concentration in circulation probably decreases, resulting in low MTX levels in liver.…”
Section: Discussionmentioning
confidence: 81%
“…FRα-mediated transport of MTX is also evident [28]. Reports on low folate induced upregulation of FR support the inverse relationship between FA concentration and FR expression [29]. In either case, MTX concentration in circulation probably decreases, resulting in low MTX levels in liver.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, recent reports have demonstrated that media and FBS conditions are critically important for response to methotrexate ( 61, 62 ). Moreover, depleting folate may increase sensitivity to antifolates ( 63, 64 ). In this regard, it is interest to speculate that depleting folate in the media or diet may more robustly affect p16/ Cdkn2a low cells either alone or in combination with antifolates.…”
Section: Discussionmentioning
confidence: 99%